Recounstructing the Customary Law of the Tidore Sultanate: Regulation of Marrige, Inheritance, and Customary Communal Land Rights - Nur ida; Nurlina Buamona; Nurlaila Kadarwati Papuluwa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study examines the reconstruction of customary law (Se-Atorang) in the Sultanate of Tidore, focusing on customary marriage, inheritance, and communal land rights. The research addresses the limited documentation of customary legal norms and the growing challenges posed by modernization and the development of national law. The objective is to analyze the existence, implementation, and reconstruction of customary legal principles that continue to regulate social relations and preserve the cultural identity of the Tidore community. This research employed an empirical legal approach with a qualitative descriptive method. Data were collected through field observations, in-depth interviews with traditional leaders and customary authorities of the Sultanate of Tidore, and document analysis. The findings demonstrate that customary law remains a living legal system that functions alongside state and Islamic law in Tidore society. The reconstruction reveals three core principles of Se-Atorang: (1) customary marriage is grounded in family consensus, religious values, and the protection of women's dignity; (2) inheritance practices primarily follow Islamic law while incorporating customary deliberation to maintain social harmony and kinship; and (3) communal land rights are preserved through collective management based on ancestral ownership and customary authority. These principles reflect the adaptability of Tidore customary law in responding to contemporary social and legal developments while maintaining local cultural values. The study highlights the importance of documenting, protecting, and integrating customary law into legal and educational frameworks to strengthen indigenous cultural heritage and ensure its sustainability for future generations.